Analyzing body composition in living kidney donors: impact on post-transplant kidney function - Quint, Evelien E.; Westenberg, Lisa B.; Nieuwenhuijs-Moeke, Gertrude J.; van den Broek, Eva A. N.; Zorgdrager, Marcel; Viddeleer, Alain R.; Bakker, Stephan J. L.; Nolte, Ija M.; van Londen, Marco; Pol, Robert A.; , TransplantLines Investigators (Frontiers in Nephrology, 2024)
Living donor kidney transplantation boasts superior patient and graft survival rates compared to deceased donor kidney transplantation. However, the impact of living donor body composition (BC) on post-transplant kidney function remains uncertain. In a cohort of 293 living kidney donor-recipients pairs, we utilized linear mixed model analyses, adjusted for time and including a multiplicative interaction term of time with the donor body composition measure, and found no significant associations between any donor BC measure and the annual change in recipient post-transplantation estimated glomerular filtration rate (eGFR) [donor body mass index (BMI): B=-0.01, 95%CI -0.13; 0.11, p=0.88; donor waist circumference: B=0.02, 95%CI -0.02; 0.06, p=0.38; donor skeletal muscle index: B=-0.02, 95%CI -0.07; 0.04, p=0.63; donor skeletal muscle radiation attenuation: B=-0.002, 95%CI -0.06; 0.06, p=0.96; donor visceral adipose tissue index: B=-0.001, 95%CI -0.02; 0.02, p=0.93; donor subcutaneous adipose tissue index: B=-0.001, 95%CI -0.02; 0.02, p=0.94; donor intramuscular adipose tissue index: B=-0.12, 95%CI -0.29; 0.06, p=0.19; donor total abdominal adipose tissue index: B=-0.001, 95%CI -0.01; 0.01, p=0.89]. Our study suggests that pre-donation BC does not affect post-transplantation recipient eGFR in donor populations with a BMI below 35 kg/m2.